Advancing dental education: feedback processes in the clinical learning environment. Issue 1 (2nd January 2020) - Adam, Lee A.; Oranje, Jo; Rich, Alison M.; Meldrum, Alison
ABSTRACT: Feedback plays an important role in students' learning. The clinical dental teaching and learning environment is challenging; tutors supervise students undertaking irreversible procedures on patients. Situations arise where 'good' teaching practices may take second place to ensuring patient, student, and tutor safety. This research aimed to investigate the specific factors impacting clinical tutors' desire and ability to give effective feedback to students. It reports data from interviews with clinical teachers at the University of Otago Faculty of Dentistry. The data were analysed inductively, and four themes were identified: (i) Feedback as a teaching moment, where tutors used the terms feedback and teaching interchangeably and viewed feedback as their primary mode of teaching in the clinical environment; (ii) time, where tutors spoke about time constraints in the clinic that made it difficult to engage with students in the depth they would like; (iii) empathy and respect where tutors were mindful that the students were emerging professionals and should be treated as the tutors wished to be treated themselves; (iv) and self-reflection where the tutors reflected on their own teaching practices in order to improve them. Findings will inform ongoing improvements to institutional processes that can help improve student outcomes.